Eficácia do rofecoxibe e do diclofenaco sódico no controle da dor, edema e trismo em exodontias dos terceiros molares inferiores - Ramos, Tercio Carneiro (2004)
New selective COX-2 inhibitors non-steroidal antiinflammatory agents have been used with great approval by clinicians and patients. This work evaluated the therapeutic efficacy and the costs of the rofecoxib 50 mg/day, p.o. treatment compared to diclofenac sodium 50 mg, p.o 8/8h in the control of pain, swelling and trismus during the postoperative of the third lower molar exodontia in 59 patients, 30 in the rofecoxib group and 29 in the diclofenac sodium group. The assessment were made during the preoperative, 30 minutes after the surgical procedure, which corresponded with the administration of the drugs, and 0.5; 1.0; 2.0; 24; 48; 72 and 192h after the drugs administration. The rofecoxib provided a higher analgesia than diclofenac when the symptom pain was evaluated by a distinguished scale. In proportion, after the intervals of 1 and 2 hours, 50 and 60.71% of the patients in the rofecoxib group and 14.28 and 25.92% in the diclofenac group, respectively, referred complete analgesia. This difference was statistically significant (p<0.05). When the assessment was made by the EVA analogical visual scale, the diclofenac group pain scores were higher than rofecoxib after 1 and 2 hours. This difference was also statistically significant (p<0.05). The use of the rescue medication in the rofecoxib was significative lower compared with diclofenaco group (p<0.05). When Rofecoxib was compared to diclofenac, presented higher averages of swelling. This difference was statistically (p<0.05) 48h after the surgical procedure. There was no statistically significant difference in the trismus control with the use of the medications. Rofecoxib presents a higher cost of 257.49% if compared to the treatment of generic diclofenac and 73.06% if compared to Voltaren. When indicated a gastric protector associated to diclofenac, the rofecoxib is the most economic option isolated.